PERAN NEGARA DALAM PEREKONOMIAN MENURUT PEMIKIRAN IBNU TAIMIYAH DAN RELEVANSINYA TERHADAP SISTEM PEMBANGUNAN EKONOMI DI INDONESIA - Farhan Zaki A; Addiarrahman; Muhammad Ismail (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This thesis discusses and aims to know about the Role of the State in the Economy According to Ibn Taimiyah's Thoughts and Its Relevance to the Economic Development System in Indonesia. The approach used in this research is the literature approach which is a type of descriptive qualitative research. In this study, the researcher conducteda study of Ibn Taimiyah's views on the role of the state and its relevance to the economic system in Indonesia. The study in this paper is a type of literature study, which is looking for written material and other reading materials related to the topic discussed to study and analyze library sources in more detail to obtain research data. The results showed that 1. The role of the state described by Ibn Tamiyyah focuses on the concept of comprehensive justice in every circle, so that where there is a fair and comprehensive opportunity that each group and individual have, because there is the same opportunity that each group or individual has, causes a turnover of funds for community activities and the role of the government so that there is no market monopoly activity so as not to cause a high price of goods Certainly, so that this will have a good impact on the existing economic system, the government must also think about how to eliminate the gaps in a country, control market regulations, determine monetary policy so that there is no inflantion and deflection, and carry out economic planning so that it can fulfill social and group policies, by developing state infrastructure. 2. Furthermore, regarding the relevance of the development system according to Ibn Tamiyyah in Indonesia, there are several things that occur in the Indonesian government which are the application of fair currency values, infrastructure development, monetera policies carried out by the government and running the existing pendidi kan system for the importance of future generations..